1989
DOI: 10.1002/bit.260340209
|View full text |Cite
|
Sign up to set email alerts
|

Effect of number of turbine impellers on surface aeration in laboratory fermentor

Abstract: The effect of one and two four-flat-bladed turbine impellers on the surface aeration intensity in a laboratory tormentor was investigated at different agitation speeds and sparge rates. The surface aeration was found to be generally more intensive with two impellers for the same other operating conditions because of higher power consumption and the position of the upper impeller closer to the free liquid surface. The surface aeration intensity was successfully correlated in terms of power consumption and sparg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…For unsparged vessels, Matsumura et al (1982a) have Veljkovic and Skala (1989) have shown that, QsA a Ph5 Q, Veljkovic et al (1991) Rushton Turbine From the above comparison, it can be seen that there is a large discrepancy between the various authors even about the dependancy of the effect of impeller speed and the impeller diameter on the rate of surface aeration. The rate of surface aeration, QsA a N1.9 lo s, and QsA 0: D4 7.…”
Section: Recommendationsmentioning
confidence: 89%
See 4 more Smart Citations
“…For unsparged vessels, Matsumura et al (1982a) have Veljkovic and Skala (1989) have shown that, QsA a Ph5 Q, Veljkovic et al (1991) Rushton Turbine From the above comparison, it can be seen that there is a large discrepancy between the various authors even about the dependancy of the effect of impeller speed and the impeller diameter on the rate of surface aeration. The rate of surface aeration, QsA a N1.9 lo s, and QsA 0: D4 7.…”
Section: Recommendationsmentioning
confidence: 89%
“…A similar technique for the measurement of the rate of surface aeration was used by Topiwala (1972), Veljkovic and Skala (1989) and Veljkovic et al (1991). Matsumura et al (1982a) have measured the rate of absorption by surface aeration for unsparged vessels.…”
Section: Rate Of Surface Aerationmentioning
confidence: 98%
See 3 more Smart Citations